Class ebook A memoir of motherhood, hunger, and higher education. - Land, Stephanie (2023)
NATIONAL BESTSELLER A Good Morning America Book Club Pick A New York Times Most Anticipated Books of Fall From the New York Times bestselling author who inspired the hit Netflix series about a struggling mother barely making ends meet as a housecleaner, a "raw and inspiring" ( People ) memoir about college, motherhood, poverty, and life after Maid . When Stephanie Land set out to write her memoir Maid , she never could have imagined what was to come. Handpicked by President Barack Obama as one of the best books of 2019, he called it an "unflinching look at America's class divide...and a reminder of the dignity of all work." Later, it was adapted into the hit Netflix series Maid , which was viewed by sixty-seven million households and was Netflix's fourth most-watched show in 2021, garnering three Primetime Emmy Award nominations. Stephanie's escape out of poverty and abuse in search of a better life inspired millions. Maid was a story about a housecleaner, but it was also a story about a woman with a dream. In Class , Land takes us with her as she finishes college and pursues her writing career. Facing barriers at every turn including a byzantine loan system, food insecurity, the judgments of professors and fellow students who didn't understand the demands of attending college while under the poverty line—Land finds a way to survive once again, finally graduating in her mid-thirties. Class paints an intimate and heartbreaking portrait of motherhood as it converges and often conflicts with personal desire and professional ambition. Who has the right to create art? Who has the right to go to college? And what kind of work is valued in our culture? In clear, candid, and moving prose, Class grapples with these questions, offering a searing indictment of America's educational system and an inspiring testimony of a mother's triumph against all odds.